Treatment outcome of multiple myeloma (MM) based on cytogenetic risk stratification: a single institute experience from south India - Bhat, Guruprasad (International Journal of Advances in Medicine, 2019)
Background: To study the epidemiology, incidence and the clinical outcome of multiple myeloma (MM) among the patients based on the cytogenetic risk stratification. Methods: Author retrospectively analysed 50 patients of Multiple Myeloma (MM) with conventional cytogenetics and interphase Fluorescence In-Situ Hybridization (FISH) method and author classified the risk on the mSMART classification. Treatment and outcome were evaluated separately based on the cytogenetic risk stratification for three arms of treatment- Bortezomib, Thalidomide and Dexamethasone (BTD), Thalidomide and Dexamethasone (TD) and Lenalidomide and Dexamethasone (LD). Results: The median age of the patients was 61years (48-74years) and ratio between male to female was 1.5:1. The overall response (OR) rate among high risk patients treated with Bortezomib, Thalidomide and Dexamethasone (BTD) was 100% with Complete Response (CR) being 26.7%. The OR rate and CR rates among standard risk treated with Thalidomide and Dexamethasone (TD) and Lenalidomide and Dexamethasone (LD) were 61%, 11% and 76%, 18% respectively. The two years overall survival (OS) was 53.3% in high risk and 66.7% with Thalidomide and Dexamethasone (TD) and 76.5% with Lenalidomide and Dexamethasone (LD) in low risk group. Conclusions: The present study showed that the high-risk features of cytogenetics portend poor outcome among MM patients. Bortezomib, Thalidomide and Dexamethasone (BTD) based therapy have improved the Overall Response (OR) rate and Complete Response (CR) rates in high risk MM, however overall survival (OS) is poor in this risk strata. The study also showed that cytogenetic risk stratification and the outcome of myeloma do correlated with each other.